Energy Subsidy Reform in Sub-Saharan Africa : Experiences and Lessons - Alleyne, Trevor (Departmental Papers; Departmental Paper, 2013)
The reform of energy subsidies is an important but challenging issue for sub-Saharan African (SSA) countries. There is a relatively large theoretical and empirical literature on this issue. While this paper relies on that literature, too, it tailors its discussion to SSA countries to respond to the following questions: Why it is important to reduce energy subsidies? What are the difficulties involved in energy subsidy reform? How best can a subsidy reform be implemented? This paper uses various sources of information on SSA countries: quantitative assessments, surveys, and individual (but standardized) case studies.